Financial liberalisation and economic growth in sub-Saharan African countries : dilemmas and prospects - Odhiambo, Nicholas Mbaya (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--Stellenbosch University, 2004.